Theories of cosmic time in the Mahābhārata - Thomas, LK (1987)
This thesis presents an examination of the Indian theories of cosmic time as they are found in the Mahabharata. It looks at the theories in detail and analyses their essential characteristics and structures of its three main elements: the divisions of time; the cycle of creation and destruction; and the characteristics of the four yugas. Special attention is paid to aspects of the theory that have been little explored, such as the nature of the cyclical repetition; the relationship between the yugas and the avataras of Visnu; the characteristics of the junctures between the yugas, etc. In the few areas where the theories of cosmic time found in the Mahabharata differ from those of the Purad nas, the differences are indicated. Ideas of cosmic time in literature preceding the Mahabharata are examined, and it is argued that the fundamental structures and concerns of the later theories can be seen to have clear antecedents in the cosmogony of the Vedas and the cosmogonic implications of certain sacrifices found in the Brahmad nas: Vedic cosmogonies show that the primary creative act is the imposition of order on chaos, in the spatial, temporal and ethical spheres, and the sacrifices show the existence of a cycle of creation and destruction, where creation must be periodically re-established by the sacrifice and the sacrificer. These principles are seen to still inform the later theories, and often help to throw light on obscure areas within them.